Current State and Issues of Regenerative Medicine for Rheumatic Diseases - Yoshimi, Ryusuke; Nakajima, Hideaki (Frontiers in Medicine, 2022)
The prognosis of rheumatic diseases is generally better than that of malignant diseases. However, some cases with poor prognoses resist conventional therapies and cause irreversible functional and organ damage. In recent years, there has been much research on regenerative medicine, which uses stem cells to restore the function of missing or dysfunctional tissues and organs. The development of regenerative medicine is also being attempted in rheumatic diseases. In diseases such as systemic sclerosis (SSc), systemic lupus erythematosus (SLE), and rheumatoid arthritis, hematopoietic stem cell transplantation has been attempted to correct and reconstruct abnormalities in the immune system. Mesenchymal stem cells (MSCs) have also been tried for the treatment of refractory skin ulcers in SSc using the ability of MSCs to differentiate into vascular endothelial cells and for the treatment of systemic lupus erythematosus SLE using the immunosuppressive effect of MSCs. CD34-positive endothelial progenitor cells (EPCs), which are found in the mononuclear cell fraction of bone marrow and peripheral blood, can differentiate into vascular endothelial cells at the site of ischemia. Therefore, EPCs have been used in research on vascular regeneration therapy for patients with severe lower limb ischemia caused by rheumatic diseases such as SSc. Since the first report of induced pluripotent stem cells (iPSCs) in 2007, research on regenerative medicine using iPSCs has been actively conducted, and their application to rheumatic diseases is expected. However, there are many safety issues and bioethical issues involved in regenerative medicine research, and it is essential to resolve these issues for practical application and spread of regenerative medicine in the future. The environment surrounding regenerative medicine research is changing drastically, and the required expertise is becoming higher. This paper outlines the current status and challenges of regenerative medicine in rheumatic diseases.